Pengaruh Model Discovery Learning Berbantuan Video Animasi terhadap Pemahaman Materi Sumber Energi pada Siswa Kelas IV SD IT Luqman Al Hakim Yogyakarta - Robi'ah Al Adabiyah; Anita Ekantini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Conceptual understanding is one of the essential competencies that students should master in elementary science learning, particularly in the topic of energy sources, which contains abstract concepts. One instructional approach that can enhance students' conceptual understanding is the implementation of the Discovery Learning model supported by animated videos. This study aimed to determine the effect of the Discovery Learning model assisted by animated videos on fourth-grade students' understanding of energy source material at SD IT Luqman Al Hakim Yogyakarta. This research employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The sample consisted of 24 fourth-grade students selected through the total sampling technique. Data were collected using a validated and reliable multiple-choice test and analyzed using descriptive statistics, the Shapiro-Wilk normality test, a paired sample t-test, and the Normalized Gain (N-Gain) test. The results showed that the mean pretest score increased from 57.63 to 82.92 on the posttest. The paired sample t-test indicated a significance value of 0.000 (p < 0.05), confirming that the implementation of the Discovery Learning model assisted by animated videos had a significant effect on students' understanding of energy source material. Furthermore, the average N-Gain score was 0.602, which was categorized as moderate. These findings indicate that the Discovery Learning model assisted by animated videos is effective as an alternative instructional approach to improve elementary students' conceptual understanding in science learning.